Digest: Disentangling plumage and behavior contributions to iridescent signals. (31st January 2019) - Gruson, Hugo
Abstract: To what extent do plumage properties and behavior interact to produce visual signals? Simpson and McGraw (2019) propose an elegant and novel experimental set‐up to dissociate behavior and color and assess their relative effects in the resulting iridescent signal. They find that modification of either component leads to a modification of the resulting signal as seen by the receiver, suggesting that sexual selection acts simultaneously on both signal components.